ANALISIS KETERAMPILAN ARGUMENTASI SISWA SMP BERBANTUAN SOCIO-SCIENTIFIC ISSUE PEMANASAN GLOBAL - Sofinatul Zairina; Siti Nurul Hidayati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aims to analyze the quality of argumentation skills of junior high school students using the help of socio-scientific issues articles on global warming material. This study adopted a cross-sectional survey design research method with a one-shot survey or test. This study involved 30 seventh grade students of SMPN 62 Surabaya who had received learning materials on global warming. Data collection is based on random sampling technique using a description test instrument with SSI articles. The data analysis technique used in this research is descriptive statistical analysis. The results showed that the quality of students' argumentation skills was still at level 1 and level 2. Based on the argumentation indicators according to Toulmin's Argumentation Pattern, the overall student's argumentation ability was in the poor category, with an average percentage of 57.33% with exposure to each argumentation aspect, claim aspect. in the sufficient category with an average percentage of 63.33%, the data aspect in the less category with an average percentage of 58.88%, the warrant aspect in the less category with an average percentage of 58.88%, the backing aspect in the less with an average percentage of 54.44%, and the qualifier aspect in the less category with an average percentage of 51.11%. The written argumentation skills of seventh grade students of SMP Negeri 62 Surabaya are still relatively low.